2020
DOI: 10.1002/jmv.26681
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine in COVID‐19 patients: Thinking out of the box

Abstract: Coronavirus disease 2019 , identified as the disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), was recognized as a public health emergency by World Health Organization, and declared a pandemic on March 11, 2020. Symptoms of respiratory tract infection along with signs of the systemic inflammatory response, represent its dominant manifestation, however, extra-respiratory symptoms including abdominal pain, diarrhea, symptoms of pericarditis, or severe myalgias have been AUTHOR CONTR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…We previously reported that ( R,S )-ketamine produced a potent anti-inflammatory effects in treatment-resistant patients with depression [ 80 ]. Collectively, it is proposed that ( R,S )-ketamine may have beneficial effects for patients infected with SARS-CoV-2 [ 81 , 82 ]. At present, an open label study of ( R,S )-ketamine in patients infected with SARS-CoV-2 (ClinicalTrials.gov Identifier: NCT04365985) at Williams Beaumont Hospital (Michigan, USA) is underway.…”
Section: Other Candidate Cutamesine and Arketaminementioning
confidence: 99%
“…We previously reported that ( R,S )-ketamine produced a potent anti-inflammatory effects in treatment-resistant patients with depression [ 80 ]. Collectively, it is proposed that ( R,S )-ketamine may have beneficial effects for patients infected with SARS-CoV-2 [ 81 , 82 ]. At present, an open label study of ( R,S )-ketamine in patients infected with SARS-CoV-2 (ClinicalTrials.gov Identifier: NCT04365985) at Williams Beaumont Hospital (Michigan, USA) is underway.…”
Section: Other Candidate Cutamesine and Arketaminementioning
confidence: 99%
“…Dexmedetomidine is commonly used in combination with ketamine during anesthesia and ventilation support during mechanical ventilation (Luscri and Tobias 2006 ). Ketamine also inhibits release of HMGB1 and NETs formation during ALI (Akinosoglou et al 2020 ). Further, ketamine has been shown to attenuate sepsis-induced ALI by down-regulating the HMGB1-RAGE pathway (Zhang et al 2018 ).…”
Section: Extracellular Hmgb1 Inhibitorsmentioning
confidence: 99%
“…Its use has been described, with intranasal esketamine self-administered under clinical supervision via telemedicine [153]. The use of ketamine/ intravenous/intranasal esketamine in depressive episodes related to neuropsychiatric complications of COVID-19 should not be overlooked [154]. Ketamine seems to derive its therapeutic action, at least in part, from a decrease in the production of pro-inflammatory cytokines, including IL-6, involved in the immunopathology of COVID-19 [154].…”
Section: Management Of Resistant Depression With Covid-19mentioning
confidence: 99%